Opticoneuromyelitis associated with melanoma. Case report - Valentina V. Gudkova; Ekaterina I. Kimelfeld; Vera P. Paderina; Dmitrii S. Koshurnikov; Dmitrii I. Ulianov; Dmitrii S. Ermakov; Nadezhda A. Maliutina (ZAO "Consilium Medicum", 2021)
This article presents a clinical review of a patient with an extremely rare assotiation of opticoneuromyelitis and skin melanoma. The paper noted the typical clinical and neuroimaging signs of opticoneuromyelitis and the rare manifestations of myelitic syndrome such as segmental muscle hypertonicity and hand hyperkinesis. The question remains open as to whether these two processes in a patient are linked by a single pathogenesis in the form of a paraneoplastic neurological syndrome or whether two independent diseases are represent there. Two observations of a combination of melanoma and opticoneuromyelitis as a manifestation of the paraneoplastic syndrome have been analysed in the literature. The article highlights the difficulties in the treatment of this patient, as the immunomodulatory therapy used for both diseases has a different vectorial focus. Immunosuppression is recommended for the treatment of opticoneuromyelitis, while immune activation is recommended for melanoma.